Legal adaptation of the Corona pandemic as a force majeure or an emergency in Iraqi and comparative law - Assistant Lecturer Saher Nasser Hussein Alazzawi; PHD Saeed Yousef Saeed Al Bustani (The college of law and political science journal, 2024)
The emerging Corona pandemic has constituted an unprecedented global health crisis, and the effects of this pandemic and the precautionary measures to confront it have extended to the process of implementing contracts in general and the process of implementing civil contracts in particular, and the law constitutes the first and most capable weapon to confront these effects, by applying the theory of force majeure when the implementation of the contract becomes impossible, or by applying the theory of emergency circumstances when the implementation of the contract becomes burdensome for the contracting party, and therefore we have researched and clarified the importance of accurate and correct legal adaptation of this pandemic and its effects, whether as Force Majeure.